Our Impossible Love - Durjoy Dutta (Penguin Books India, 2016)
A romantic bestseller, Our Impossible Love is centered around the growing up years of a young Aisha, her journey of self-discovery as a woman and love. She is living with her brother and ailing mother whereas her father lives and works in a different city. The family is a close knit one but has a tough time in meeting the medical bills of the mother. For Aisha, her growing up is centered around brother, mother and close friends Namrata and Norbu. As children, the brother-sister relationship is a close one, where sharing and playing together is great fun, but as they grow up, gaps appear and the brother begins to remain aloof and quiet in himself. As a result of increasing gap, their relationship drifts apart. On the day Aisha turns eighteen, the birthday party date turns out to be a horror. All was well with Vibhor, her date for the evening, till something terrible happens. The experience leaves her devastated. Danish, a young man is in awe of his younger brother, who is ambitious and an overachieving individual. He already feels lost out who may never find a woman to love. Being appointed as a counselor to Aisha at school changes all that. The two begin to develop chemistry. The love story and relationships get more complex when the family learns that Aishas brother is gay. After the initial shock, the childhood sibling love comes to the fore and the family comes around to understand the complex nature of the young man. Our Impossible Loves explores human relationships in all their complexity, juxtaposing a manwoman relationship with a brother-sister love and that of gay love. Durjoy Datta, a master craftsman at storytelling, has created characters in a urban setting that are easy to relate to, where achieving a balance between life, love and ambition is not always an easy task.